Analisis Pemahaman Konsep Matematika Peserta Didik Dalam Menyelesaikan Soal Pada Materi Penjumlahan Bersusun Kelas II SD Negeri 15 Segedong - Julaiha Julaiha (Jurnal Pendidikan Indonesia (JOUPI), 2024)
The aim of this research is to analyze students’ ability to understand mathematical concepts. This research uses qualitative research with descriptive methods. This research was carried out at SD Negeri 15 segedong for the 2023/2024 academic year in class II. The data sources for this research are test results and checklist sheets. The research results showed that students’ understanding of mathematical concepts in the high category was 8,6%, in the medium category was 13%, and in the low category was 78,2%. The results of this research also show that the performance of students from each category is as follows: (a) students in the high category can meet 2 indicators out of 3 indicators of understanding mathematical concepts, (b) students in the medium category can meet 1 indicators out of 3 indicators of understanding mathematical concepts, (c) students in the low category cannot meet all indicators of understanding of mathematical concepts used. Research results show that students’ understanding cannot master all indicators of understanding of the mathematical concepts, namely translation, intrapolation and extrapolation.